Robust design of a damping controller for static VAr compensators in power systems. - Xuechun Yu (IEEE Transactions on power systems)
This paper presents a systematic procedure for the synthesis of a supplementary damping controller (SDC) for static VAr compensators (SVC) in multimachine power systems. The robust performance in terms of the structured singular value (SSV or μ) is used as the measure of control performance. A wide range of operating conditions are used for testing. Simulation results on standard test systems show that the resulting SDC effectively enhances the damping of the interarea oscillations, providing robust stability and good performance characteristics both in frequency domain and in time domain